Contest pieces for trumpet or cornet and piano - Mellet, Jean-Joseph 1843-1910; Salomon, Hector 1838-1906; Jonas, Emile 1827-1905; Alary, Georges; Erlanger, Camille 1863-1919; Thomé, Francis 1850-1909; Gaubert, Philippe 1879-1941; Balay, Guillaume 1871-1943 (A-R Special Publications, 2015)
A collection of pieces composed for students of the Paris Conservatoire